Quality of provider-client interaction in a reproductive health clinic in Isabela, Philippines - Rosalinda S. Guingab; Pedrita N. Medrano (Intelektual Pustaka Media Utama, 2021)
The quality of provider-interaction determines client satisfaction and decision to seek health care. This research aimed to determine the women clients’ perception of their quality of interaction with the health care providers in a government reproductive health clinic in one of the municipalities in northern Philippines. Respondents consisted of 30 pregnant women who had visited the clinic for prenatal health care check-up were interviewed. A structured questionnaire and a semi-structured guided for probing served as the study’s research instruments. Women perceived the health care providers to possess good communication skills, and had displayed behavior that showed a regard for them. However, the providerinteraction was considered to be unilinear, with the provider perceived to have dominated the interface, The women also perceived only a somewhat evident show of sympathy/empathy. Hostile words were heard frequently. Creation of a two-way interaction with respect for their clients must be considered by the health care providers. Policies must also be formulated to improve the quality of provider-client interaction inside reproductive health clinics.